2022
DOI: 10.1371/journal.pone.0261035
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of molecular signatures reveals a hybrid approach in breast cancer: Combining the Nottingham Prognostic Index with gene expressions into a hybrid signature

Abstract: The diagnosis of breast cancer—including determination of prognosis and prediction—has been traditionally based on clinical and pathological characteristics such as tumor size, nodal status, and tumor grade. The decision-making process has been expanded by the recent introduction of molecular signatures. These signatures, however, have not reached the highest levels of evidence thus far. Yet they have been brought to clinical practice based on statistical significance in prospective as well as retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…To achieve more precise predictions, it may be necessary to refine prognostic models by incorporating multiple complementary factors. Our recent research has demonstrated that a hybrid model that integrates gene expression and clinical information can significantly improve prognostic power 20 . This approach has also been highlighted in various studies on cancer prognosis [37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve more precise predictions, it may be necessary to refine prognostic models by incorporating multiple complementary factors. Our recent research has demonstrated that a hybrid model that integrates gene expression and clinical information can significantly improve prognostic power 20 . This approach has also been highlighted in various studies on cancer prognosis [37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…If we have more samples, it is possible to confirm this hypothesis. Furthermore, in many cases, molecular classifications have been confirmed to be more robust in predicting survival rates than conventional histopathology methods 24–28 . With the development of more advanced molecular methods, it is possible to develop clinically relevant and practical molecular signatures 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in many cases, molecular classifications have been confirmed to be more robust in predicting survival rates than conventional histopathology methods. [24][25][26][27][28] With the development of more advanced molecular methods, it is possible to develop clinically relevant and practical molecular signatures. 29,30 Proliferation and cell cycle-based gene signatures have been vastly assessed to determine molecular subtypes and to predict the clinical outcome in different human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These changes would not have been expected from the gene expression data because the effects regarding elongases (that leads to increased chain length) are weak. This fact emphasizes that the exclusive consideration of changes in the genome is a not very reliable approach, but experimental compositional data are also required (a similar conclusion that gene expression data is not su cient as a single signature was also made by [32]). Additionally, even if changes in the protein levels often accompany changes in the genes, the concentrations alone are not indicative.…”
Section: Experimental Lipid Analysismentioning
confidence: 93%